Examples with solutions for Power of a Product: Variable in the base of the power

Exercise #1

(5x3)3= (5\cdot x\cdot3)^3=

Video Solution

Step-by-Step Solution

We use the formula:

(a×b)n=anbn (a\times b)^n=a^nb^n

(5×x×3)3=(15x)3 (5\times x\times3)^3=(15x)^3

(15x)3=(15×x)3 (15x)^3=(15\times x)^3

153x3 15^3x^3

Answer

153x3 15^3\cdot x^3

Exercise #2

(y×x×3)5= (y\times x\times3)^5=

Video Solution

Step-by-Step Solution

We use the formula:

(a×b)n=anbn (a\times b)^n=a^nb^n

(y×x×3)5=y5x535 (y\times x\times3)^5=y^5x^53^5

Answer

y5×x5×35 y^5\times x^5\times3^5

Exercise #3

(ab8)2= (a\cdot b\cdot8)^2=

Video Solution

Step-by-Step Solution

We use the formula

(a×b)x=axbx (a\times b)^x=a^xb^x

Therefore, we obtain:

a2b282 a^2b^28^2

Answer

a2b282 a^2\cdot b^2\cdot8^2

Exercise #4

(a56y)5= (a\cdot5\cdot6\cdot y)^5=

Video Solution

Step-by-Step Solution

We use the formula:

(a×b)x=axbx (a\times b)^x=a^xb^x

Therefore, we obtain:

(a×5×6×y)5=(a×30×y)5 (a\times5\times6\times y)^5=(a\times30\times y)^5

a5305y5 a^530^5y^5

Answer

a5305y5 a^5\cdot30^5\cdot y^5

Exercise #5

Insert the corresponding expression:

(c×b×a)2= \left(c\times b\times a\right)^2=

Video Solution

Step-by-Step Solution


Step 1: The problem provides the expression (c×b×a)2 \left(c \times b \times a\right)^2 and asks us to expand it.
Step 2: We'll use the exponent rule for the power of a product, which states that (xyz)n=xn×yn×zn (xyz)^n = x^n \times y^n \times z^n . Applying this rule to our expression, we get:
(c×b×a)2=c2×b2×a2 \left(c \times b \times a\right)^2 = c^2 \times b^2 \times a^2
Since multiplication is commutative, the order of the factors doesn't affect the product. Therefore, the expression can also be written as:
(c×b×a)2=a2×b2×c2 \left(c \times b \times a\right)^2 = a^2 \times b^2 \times c^2

Therefore, the correct expressions are c2×b2×a2 c^2 \times b^2 \times a^2 and a2×b2×c2 a^2 \times b^2 \times c^2 .

Answer

a'+b' are correct

Exercise #6

Insert the corresponding expression:

(6×b)4= \left(6\times b\right)^4=

Video Solution

Step-by-Step Solution

The problem requires us to simplify (6×b)4(6 \times b)^4.

  • Step 1: Recognize that (6×b)(6 \times b) is a product of two factors 66 and bb.
  • Step 2: Apply the Power of a Product Rule, which states that (ab)n=an×bn(ab)^n = a^n \times b^n.

Let's apply this rule to (6×b)4(6 \times b)^4:
Using the rule, we distribute the exponent 44 to each component of the product:

(6×b)4=64×b4 (6 \times b)^4 = 6^4 \times b^4

Thus, the expression simplifies to 64×b46^4 \times b^4.

Therefore, the simplified expression is:

64×b46^4 \times b^4.

Answer

64×b4 6^4\times b^4

Exercise #7

Insert the corresponding expression:

(b×9×a)6= \left(b\times9\times a\right)^6=

Video Solution

Step-by-Step Solution

To expand the expression (b×9×a)6 \left(b \times 9 \times a\right)^6 , we'll apply the power of a product rule for exponents, which states that (xyz)n=xn×yn×zn (xyz)^n = x^n \times y^n \times z^n .

  • Step 1: Identify each factor within the base: b b , 9 9 , and a a .
  • Step 2: Apply the exponent to each factor individually:
    • b6 b^6
    • 96 9^6
    • a6 a^6

By multiplying these results together, the expanded form is b6×96×a6 b^6 \times 9^6 \times a^6 .

Therefore, the correct expression is b6×96×a6 b^6 \times 9^6 \times a^6 .

Answer

b6×96×a6 b^6\times9^6\times a^6

Exercise #8

Insert the corresponding expression:

(2×x)2= \left(2\times x\right)^2=

Video Solution

Step-by-Step Solution

To solve the expression (2×x)2(2 \times x)^2, we'll follow these steps:

  • Step 1: Identify the base of the exponent, which is the product 2×x2 \times x.
  • Step 2: Apply the Power of a Product rule, which states that (ab)n=an×bn(ab)^n = a^n \times b^n.
  • Step 3: Distribute the exponent to both factors within the parentheses:

(2×x)2=22×x2(2 \times x)^2 = 2^2 \times x^2

Calculating 222^2 gives:

22=42^2 = 4

So, the expression simplifies to:

4×x24 \times x^2

Therefore, the correct expression is 22×x22^2 \times x^2.

This corresponds to Choice 2.

Answer

22×x2 2^2\times x^2

Exercise #9

Insert the corresponding expression:

(5×b×a)4= \left(5\times b\times a\right)^4=

Video Solution

Step-by-Step Solution

To solve the expression (5×b×a)4 \left(5 \times b \times a\right)^4 , we'll apply the Power of a Product Rule, which states that when a product is raised to an exponent, each factor in the product is raised to that exponent individually.

  • First, identify each factor in the product: 5 5 , b b , and a a .

  • Next, apply the exponent to each factor:

    • The number 5 5 becomes 54 5^4 .

    • The variable b b becomes b4 b^4 .

    • The variable a a becomes a4 a^4 .

  • Finally, multiply these results together to obtain the simplified expression.

Therefore, the expression (5×b×a)4 \left(5 \times b \times a\right)^4 simplifies to 54×b4×a4 5^4 \times b^4 \times a^4 , which corresponds to Choice 3.

Answer

54×b4×a4 5^4\times b^4\times a^4

Exercise #10

Insert the corresponding expression:

(a×3)3= \left(a\times3\right)^3=

Video Solution

Step-by-Step Solution

To solve the problem (a×3)3 (a \times 3)^3 , we'll apply the power of a product rule which states that (xy)n=xnyn(x \cdot y)^n = x^n \cdot y^n.

Step 1: Identify the individual factors within the parentheses. In this expression, aa and 3 are multiplied together and are being raised to the power of 3.

Step 2: Apply the power of a product property: Distribute the exponent of 3 to both aa and 3 inside the parentheses. We do so as follows:
(a×3)3=a3×33(a \times 3)^3 = a^3 \times 3^3

Step 3: Express the result clearly. The expression simplifies to:
a3×33a^3 \times 3^3.

Therefore, the correct answer to this problem is a3×33 a^3 \times 3^3 .

Answer

a3×33 a^3\times3^3

Exercise #11

Insert the corresponding expression:

(a×b)3= \left(a\times b\right)^3=

Video Solution

Step-by-Step Solution

To solve the problem (a×b)3 \left(a \times b\right)^3 , we'll apply the rules of exponents, specifically the Power of a Product rule.

  • Step 1: Understand the Power of a Product Rule
    The Power of a Product rule states that when you raise a product to an exponent, you can apply the exponent to each factor inside the parentheses individually. Mathematically, this is expressed as: (a×b)n=an×bn \left(a \times b\right)^n = a^n \times b^n

  • Step 2: Apply the Rule to the Given Expression
    Given the expression (a×b)3 \left(a \times b\right)^3 , we can apply the Power of a Product rule by raising each factor inside the parentheses to the power of 3: (a×b)3=a3×b3 \left(a \times b\right)^3 = a^3 \times b^3

  • Step 3: Simplify the Expression
    After applying the exponent to both a a and b b , the expression simplifies to: a3×b3 a^3 \times b^3

Therefore, the corresponding expression for (a×b)3 \left(a \times b\right)^3 is a3×b3 a^3 \times b^3 .

Answer

a3×b3 a^3\times b^3

Exercise #12

Insert the corresponding expression:

(b×z×a)5= \left(b\times z\times a\right)^5=

Video Solution

Step-by-Step Solution

To solve the problem, we will use the rule of exponents known as the power of a product rule, which states that for any real numbers or expressions xx, yy raised to a power nn, the following holds:

(x×y)n=xn×yn(x \times y)^n = x^n \times y^n.

We have the expression (b×z×a)5 \left(b \times z \times a\right)^5 . According to the power of a product rule, we apply the exponent 5 to each factor inside the parenthesis.

Let's break it down:

  • Apply 55 to bb: (b)5=b5(b)^5 = b^5.
  • Apply 55 to zz: (z)5=z5(z)^5 = z^5.
  • Apply 55 to aa: (a)5=a5(a)^5 = a^5.

By applying the exponent to each factor, we obtain:
(b×z×a)5=b5×z5×a5 (b \times z \times a)^5 = b^5 \times z^5 \times a^5 .

Since multiplication is commutative, we can write it in any order, and a common convention is ordering it alphabetically:

Thus, a5×b5×z5 a^5 \times b^5 \times z^5 is the simplified expression.

Therefore, the correct answer to the problem is a5×b5×z5 a^5 \times b^5 \times z^5 , which corresponds to choice 1.

Answer

a5×b5×z5 a^5\times b^5\times z^5

Exercise #13

Insert the corresponding expression:

(y×a)5= \left(y\times a\right)^5=

Video Solution

Step-by-Step Solution

To solve this problem, we'll follow these steps:

  • Step 1: Identify the given information
  • Step 2: Apply the appropriate formula
  • Step 3: Perform the necessary calculations

Now, let's work through each step:
Step 1: The problem provides the expression (y×a)5 \left(y \times a\right)^5 and asks us to write the corresponding expanded expression.
Step 2: We'll use the exponent rule for the power of a product, which states that (xy)n=xn×yn (xy)^n = x^n \times y^n .
Step 3: Applying this rule, we raise each factor inside the parentheses to the fifth power: y5×a5 y^5 \times a^5 .

Therefore, the solution to the problem is y5×a5 y^5 \times a^5 .

Among the given choices, Choice 1: y5×a5 y^5 \times a^5 is the correct expression.

Answer

y5×a5 y^5\times a^5

Exercise #14

Insert the corresponding expression:

(y×x)2= \left(y\times x\right)^2=

Video Solution

Step-by-Step Solution

To solve this problem, we will apply the power of a product rule to the expression (y×x)2 (y \times x)^2 .

The power of a product rule states:

  • (a×b)n=an×bn(a \times b)^n = a^n \times b^n

In this case, the product is y×x y \times x , and the power is 2. Applying the power of a product rule gives us:

(y×x)2=y2×x2(y \times x)^2 = y^2 \times x^2

Therefore, the expanded form of the given expression is y2×x2\mathbf{y^2 \times x^2}.

Answer

y2×x2 y^2\times x^2

Exercise #15

Insert the following expression:

(y×3)2= \left(y\times3\right)^2=

Video Solution

Step-by-Step Solution

To solve this problem, we will apply the power of a product rule to the given expression (y×3)2 \left(y \times 3\right)^2 .

Let's go through the solution step-by-step:

  • Step 1: Understand the expression
    The expression (y×3)2 \left(y \times 3\right)^2 indicates that the product of yy and 33 is squared. This means we need to apply the square to both terms inside the parentheses.

  • Step 2: Apply the power of a product rule
    According to the power of a product rule: (a×b)n=an×bn(a \times b)^n = a^n \times b^n. In our case, aa is yy, bb is 33, and nn is 22. Thus, we have: (y×3)2=y2×32(y \times 3)^2 = y^2 \times 3^2.

Therefore, the correct answer to this problem is y2×32y^2 \times 3^2, which matches choice 4.

Answer

y2×32 y^2\times3^2

Exercise #16

Insert the corresponding expression:

(7×4×a)5= \left(7\times4\times a\right)^5=

Video Solution

Step-by-Step Solution

We begin by applying the power of a product rule to the expression (7×4×a)5(7 \times 4 \times a)^5.

The power of a product rule states that (x×y×z)n=xn×yn×zn(x \times y \times z)^n = x^n \times y^n \times z^n.

In this case, the expression inside the parentheses is 7×4×a7 \times 4 \times a, and it is being raised to the 5th power. We apply the exponent to each factor:

757^5

454^5

a5a^5

Therefore, the corresponding expression is 75×45×a5\boxed{7^5 \times 4^5 \times a^5}.

Answer

75×45×a5 7^5\times4^5\times a^5

Exercise #17

(y×7×3)4= (y\times7\times3)^4=

Video Solution

Step-by-Step Solution

We use the power law for multiplication within parentheses:

(xy)n=xnyn (x\cdot y)^n=x^n\cdot y^n

We apply it in the problem:

(y73)4=y47434 (y\cdot7\cdot3)^4=y^4\cdot7^4\cdot3^4

Therefore, the correct answer is option a.

Note:

From the formula of the power property mentioned above, we can understand that it applies not only to two terms within parentheses, but also for multiple terms within parentheses.

Answer

y4×74×34 y^4\times7^4\times3^4

Exercise #18

Reduce the following equation:

a8×b8×c8= a^8\times b^8\times c^8=

Video Solution

Step-by-Step Solution

To reduce the expression a8×b8×c8 a^8 \times b^8 \times c^8 , we can apply the Power of a Product Rule, which states that when multiplying powers with the same exponent across different bases, we can combine them into a single power. Specifically, this rule is written as:

(xm×ym×zm)=(x×y×z)m. (x^m \times y^m \times z^m) = (x \times y \times z)^m.

Applying this rule to our expression a8×b8×c8 a^8 \times b^8 \times c^8 , we identify x=a x = a, y=b y = b, and z=c z = c, all with the exponent m=8 m = 8 . Therefore, we can simplify the expression to:

(a×b×c)8. (a \times b \times c)^8.

Thus, the reduced form of the given expression is:

(a×b×c)8 (a \times b \times c)^8 .

Answer

(a×b×c)8 \left(a\times b\times c\right)^8

Exercise #19

Insert the corresponding expression:

43×x3×63= 4^3\times x^3\times6^3=

Video Solution

Step-by-Step Solution

To solve the problem, let's use the power of a product rule, which states that the product of several terms raised to the same power can be expressed as one parenthesis where the terms are multiplied, raised to that power.

Given the expression:

  • 43×x3×63 4^3 \times x^3 \times 6^3

We observe that all the terms 44, xx, and 66 are each raised to the power of 33. Therefore, we can represent this expression using a single power as follows:

(4×x×6)3 \left(4 \times x \times 6\right)^3

This transformation uses the formula (a×b×c)n=an×bn×cn(a \times b \times c)^n = a^n \times b^n \times c^n, taking advantage of corresponding exponents.

Therefore, the simplified expression is (4×x×6)3 \left(4 \times x \times 6\right)^3 .

Answer

(4×x×6)3 \left(4\times x\times6\right)^3

Exercise #20

Insert the corresponding expression:

32×y2= 3^2\times y^2=

Video Solution

Step-by-Step Solution

To solve the problem 32×y2= 3^2 \times y^2 = , we will make use of the power of a product rule, which helps simplify products with the same exponents.

The rule states that for any numbers a a and b b and any exponent m m , (am×bm)=(a×b)m(a^m \times b^m) = (a \times b)^m.

Using this rule, we can combine 32 3^2 and y2 y^2 into a single expression:

  • Identify the bases: We have a base of 3 and a base of y y , both raised to the power of 2.

  • Apply the formula, combining the bases under a common exponent: (3×y)2(3 \times y)^2.

This shows that 32×y2=(3×y)2 3^2 \times y^2 = \left(3 \times y\right)^2 .

Answer

(3×y)2 \left(3\times y\right)^2